The Factor Determination of Online Purchasing Decision on Indonesia Marketplace : Factor Determination of Online Purchasing Decision on Indonesia Marketplace - Rusti Kurniawati; Ginanjar Rahmawan (Journal of Research in Business, Economics, and Education, 2021)
This study aims to analyze the effect of promotion, service quality and trust in online purchasing decisions on the shopee website. The method used in sampling is nonprobability, namely purposive sampling based on considerations to adjust the criteria to improve the accuracy of the research sample, the sample was taken as many as 110 respondents using questionnaires through google form. The analysis method used in this research is the reliability test analyst, the validity test analyst, multiple regression analysis, t test, f test, and the coefficient of determination, using the calculation of the SPSS 25 application. The results show that promotion, service quality, trust have a significant effect on decisions. Purchase online on the shopee website.